1981
DOI: 10.1016/s0140-6736(81)91435-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin a and Risk of Cancer in the Western Electric Study

Abstract: Intake of dietary provitamin A (carotene) was inversely related to the 19-year incidence of lung cancer in a prospective epidemiological study of 1954 middle-aged men. The relative risks of lung cancer in the first (lowest) to fourth quartiles of the distribution of carotene intake were respectively, 7.0, 5.5, 3.0, and 1.0 for all men in the study, and 8.1, 5.6, 3.9, and 1.0 for men who had smoked cigarettes for 30 or more years. Intake of preformed vitamin A (retinol) and intake of other nutrients were not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
98
2
9

Year Published

1984
1984
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(112 citation statements)
references
References 14 publications
3
98
2
9
Order By: Relevance
“…Recent reviews (Buring & Hennekens, 1989;Fontham, 1990) have examined in detail the epidemiologic evidence relating dietary intake of beta-carotene (Graham et al, 1978;Shekelle et al, 1981;Graham et al, 1982;Wu et al, 1985;1987;Ohno et al, 1988) and of vegetable and fruit intake (MacLennan & DeCosta, 1977;Hirayama, 1979;Mettlin et al, 1979;Ziegler, 1986;Fontham et al, 1988;LeMarchand et al, 1989) to risk of specific cancers and of cancer overall. Beta-carotene has been found to be a possible protective factor for several cancers, including especially cancers of the lung, gastrointestinal tract, prostate, and breast, in some but not all epidemiologic studies (Graham et Aoki et al, 1987;Stryker et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews (Buring & Hennekens, 1989;Fontham, 1990) have examined in detail the epidemiologic evidence relating dietary intake of beta-carotene (Graham et al, 1978;Shekelle et al, 1981;Graham et al, 1982;Wu et al, 1985;1987;Ohno et al, 1988) and of vegetable and fruit intake (MacLennan & DeCosta, 1977;Hirayama, 1979;Mettlin et al, 1979;Ziegler, 1986;Fontham et al, 1988;LeMarchand et al, 1989) to risk of specific cancers and of cancer overall. Beta-carotene has been found to be a possible protective factor for several cancers, including especially cancers of the lung, gastrointestinal tract, prostate, and breast, in some but not all epidemiologic studies (Graham et Aoki et al, 1987;Stryker et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, there were many epidemiological studies [8][9][10][11][12][13][14] which have shown similar results such high dietary -carotene consumption from foods was a protective factor for certain types of cancer.…”
mentioning
confidence: 96%
“…Studies investigating serum ,Bcarotene or serum vitamin E and subsequent risk of cancer have not been published. Epidemiological studies of diet and cancer are consistent with ,Bcarotene intake being associated with a reduced risk of cancer (Peto et al, 1981: Shekelle et al, 1981 but the evidence is relatively non-specific as dietary factors other than #-carotene might well have been involved. There is some evidence based on experimental work on animals that both fl-carotene (Mathews-Roth, 1982) and vitamin E (Cook & McNamara, 1980) which plasma samples have been stored for future biochemical analysis.…”
mentioning
confidence: 97%